Propensity Score Matching Analysis of Changes in Alpha-Fetoprotein Levels after Combined Radiotherapy and Transarterial Chemoembolization for Hepatocellular Carcinoma with Portal Vein Tumor Thrombus - Jeong, Yuri (PLoS One, 2015)
BACKGROUND AND AIM: To investigate the value of changes in alpha-fetoprotein (AFP) levels for the prediction of radiologic response and survival outcomes in hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) who received combined treatment of 3-dimensional conformal radiotherapy (3D-CRT) and transarterial chemoembolization (TACE). METHODS: A database of 154 HCC patients with PVTT and elevated AFP levels (>20 ng/mL) treated with 3D-CRT and TACE as an initial treatment between August 2002 and August 2008 was retrospectively reviewed. AFP levels were determined 1 month after radiotherapy, and AFP response was defined as an AFP level reduction of >20% from the initial level. Radiologic response, overall survival (OS), and progression-free survival (PFS) rates were compared between AFP responders and non-responders. Propensity-score based matching analysis was performed to minimize the effect of potential confounding bias. RESULTS: The median follow-up period was 11.1 months (range, 3.1–82.7 months). In the propensity-score matching cohort (92 pairs), a best radiologic response of CR or PR occurred in more AFP responders than AFP non-responders (41.3% vs. 10.9%, p < 0.001). OS and PFS were also longer in AFP responders than in non-responders (median OS 13.2 months vs. 5.6 months, p < 0.001; median PFS 8.7 months vs. 3.5 months, p < 0.001). CONCLUSIONS: AFP response is a significant predictive factor for radiologic response. Furthermore, AFP response is significant for OS and PFS outcomes. AFP evaluation after combined radiotherapy and TACE appears to be a useful predictor of clinical outcomes in HCC patients with PVTT.